PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN DISIPLIN KERJATERHADAP KINERJA PEGAWAI (Studi Balai Penelitian dan Pengembangan Pengendalian Penyakit Bersumber Binatang Donggala, Kementerian Kesehatan RI) - Halimuddin, Halimuddin (Katalogis, 2015)
The study aims to seek and analysze simultaneous and partial influence of workload, work environment, and discipline on employees’ performance in The Research and Development Center of Animal Diseases Donggala. The sample consists of 40 employees, who selected to be the respondents of this research, based on census sampling technique. The study is causal descriptive, which is analyzed with multiple linear regressions. The results indicate that workload, work environment, and discipline simultaneously influence the performance of employees in The Research and Development center of Animal Diseases, Donggala. Partially, workload and discipline have significant influence on employees’ performance in The Research and Development Center of Animal Diseases, Donggala while work environment has insignificant influence on employees’ performance.